1995
DOI: 10.1111/j.1439-0388.1995.tb00550.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameter estimates for racing time by restricted maximum likelihood in the Thoroughbred horse of Japan

Abstract: Summary Genetic parameters were estimated for repeated racing times on Thoroughbred horses for several racing distances both on turf and dirt. An additive genetic and permanent environmental model of multiple‐trait derivative‐free restricted maximum likelihood (MTDFREML) was used. The data used were collected by the Japan Racing Association from 1986 to 1990 and the effects of individual race, sex, age, jockey and weight carried were used. The generation 2 pedigree information was preferable for variance estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
43
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 17 publications
10
43
7
Order By: Relevance
“…Estimates of heritability obtained from the analysis of dirt track dataset were clearly higher than those of turf track for racing time and best racing time, whereas they were similar for rank. In contrast with the current study, estimates of heritability for racing time on dirt and turf tracks were reported to be similar by OKI et al (1995). Estimates of heritability for earning traits varied from low to medium in literature.…”
contrasting
confidence: 51%
See 2 more Smart Citations
“…Estimates of heritability obtained from the analysis of dirt track dataset were clearly higher than those of turf track for racing time and best racing time, whereas they were similar for rank. In contrast with the current study, estimates of heritability for racing time on dirt and turf tracks were reported to be similar by OKI et al (1995). Estimates of heritability for earning traits varied from low to medium in literature.…”
contrasting
confidence: 51%
“…HINTZ (1980) reported lower estimate (0.15) for Thoroughbred horses and similar estimate (0.32) for Trotters compared with the current study. The estimate of heritability for racing time on dirt track (0.396) in the current study was higher than estimates of OKI et al (1995) for dirt track, which varied between 0.086 and 0.217 depending on racing distance. On the other hand, estimate of heritability for racing time on turf track (0.231) was within the range of estimates reported by OKI et al (1995) for racing time on turf track (0.081-0.254).…”
contrasting
confidence: 40%
See 1 more Smart Citation
“…The effect of environmental factors connected with specific race such as number and level of competitors, track and weather conditions may be higher for long distance races than for short distance races. Oki et al (1995) suggested that the racing performance at the different distances might be regarded as different traits. Also, a trait measured in two different environments is to be regarded as two traits (Falconer, 1989).…”
mentioning
confidence: 99%
“…However, the horse's racing performance is not always best at one racing distance. Since performance is unlikely to be constant over a distance (some horses are sprinters, some stayers, and the ability to win a 1 000m race does not imply the ability to win a 2 000m race), some authors (Oki et al, 1995;Williamson and Beilharz, 1996;Oki et al, 1997) analysed the racing performance separately in each distance range. The effect of environmental factors connected with specific race such as number and level of competitors, track and weather conditions may be higher for long distance races than for short distance races.…”
mentioning
confidence: 99%